Building effective research policy networks: linking function and form - and Mendizabal, Enrique (ODI, 2006)
This paper looks at the factors that affect the key structural characteristics of research policy networks in an attempt to develop a methodology for studying and understanding what networks do and how. It builds on previous work on the roles and functions that networks carry out and focuses on their structural characteristics. The literature on networks is explored to identify the main and most common factors affecting their structure, and then the paper considers the possible effects of these structural factors on a network's ability to perform one or more of these functions based on some of the lessons learned from a study of seven research policy networks in Peru. The paper provides a menu of factors and characteristics worth considering when intending to build effective networks.